Post-16 Further Mathematics blended learning: learner self-regulation, mathematical resilience and technology - Sofya Lyakhova (Teaching Mathematics and its Applications: An International Journal of the IMA, 2022)
This paper reports on a study set in Wales where the Further Mathematics Support Programme Wales supports the provision of an advanced qualification in mathematics for 16- to 18-year-old students with courses delivered in reduced teaching time. The study aimed to understand how the students experienced the Further Mathematics (FM) courses which are delivered either face-to-face or online and, more generally, to negotiate a place of alternative forms of delivery in post-16 mathematics curriculum. Sixteen students, eight of whom studied through the online course, were interviewed; overall, although they found the course challenging both in terms of the content and relatively limited teaching time, they enjoyed it and appeared to perceive benefits from taking the course. Most volunteered ‘tips’ about coping with the challenges of the course and the tips can be seen as strategies of self-regulation. Self-regulation strategies were reported more strongly by the students taking the course online than those attending face-to-face classes. In view of the evidence of technology creating new learning environments perceived as advantageous by students, it is hypothesized that introducing blended learning as part of post-16 mathematics curriculum could be beneficial. Improving learner self-regulation is discussed as means of improving access to FM. Other findings included the importance of support from peers, parents and schools and gender differences.